Mitochondrial transfer - a novel promising approach for the treatment of metabolic diseases - Chen, Ruijing; Chen, Jun (Frontiers in Endocrinology, 2024)
Metabolic disorders remain a major global health concern in the 21st century, with increasing incidence and prevalence. Mitochondria play a critical role in cellular energy production, calcium homeostasis, signal transduction, and apoptosis. Under physiological conditions, mitochondrial transfer plays a crucial role in tissue homeostasis and development. Mitochondrial dysfunction has been implicated in the pathogenesis of metabolic disorders. Numerous studies have demonstrated that mitochondria can be transferred from stem cells to pathologically injured cells, leading to mitochondrial functional restoration. Compared to cell therapy, mitochondrial transplantation has lower immunogenicity, making exogenous transplantation of healthy mitochondria a promising therapeutic approach for treating diseases, particularly metabolic disorders. This review summarizes the association between metabolic disorders and mitochondria, the mechanisms of mitochondrial transfer, and the therapeutic potential of mitochondrial transfer for metabolic disorders. We hope this review provides novel insights into targeted mitochondrial therapy for metabolic disorders.